KONTROL SESAR TERHADAP POLA SEBARAN URAT KUARSA DAN MINERALISASI EMAS DAERAH KUTAWARINGIN, JAWA BARAT - Wahyudiono, J.; Abdullah, C. Idham; Abidin, H. Z. (Pusat Survei Geologi, 2011)
The study area is located in Kutawaringin village, about 3.5 kilometers from Soreang city, the capital of Soreang district, Bandung regency. The purpose of this research is to show fault control on the research area that influence the distribution pattern of quartz veins and epithermal gold mineralization. Methodology in this research is initiated by literatur study. All data are compiled as overlaying maps to determine next step activities. Structural observations include macroscopic and mesoscopic. Results of the analyses are in form of structural geological map, main principal stresses distributions map and fault evolution map that could be valuable to develop a dilational zone map of the area. Structural geology investigation suggests that the main controls of the emplacement of andesit and dacite intrusive rocks as hydrothermal and metal minerals source are east-west trending dextral fault. Northwest-southeast trending normal fault are structural corridors along dilational zone. Quartz veins is distributed along dilational zone. The general trend of quartz veins is N 143°E/78°, relatively parallel to the dilational zone.Keywords : structures, dilational zone, alteration zone, mineralization, epithermal, Kutawaringin